Development of a new high-performance liquid chromatographic method for the determination of ceftazidime - Moreno, Andreia de Haro [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Aoac Int, 2008)
A rapid, accurate, and sensitive high-performance liquid chromatographic (HPLC) method was developed and validated for the determination of ceftazidime in pharmaceuticals. The method validation parameters yielded good results and included range, linearity, precision, accuracy, specificity, and recovery. The excipients in the commercial powder for injection did not interfere with the assay. Reversed-phase chromatography was used for the HPLC separation on a Waters C18 (WAT 054275; Milford, MA) column with methanol-water (70 + 30, v/v) as the mobile phase pumped isocratically at a flow rate of 1.0 mL/min. The effluent was monitored at 245 nm. The calibration graph for ceftazidime was linear from 50.0 to 300.0 mu g/mL. The values for interday and intraday precision (relative standard deviation) were < 1 %. The results obtained by the HPLC method were calculated statistically by analysis of variance. We concluded that the HPLC method is satisfactory for the determination of ceftazidime in the raw material and pharmaceuticals.